1881 Va. Acts 499, Extra Session, ch. 119, § 1, pt. 18 - (:unkn) unknown (My University, 1881)
Taxed the aggregate value of all shot-guns, rifles, muskets, and other fire-arms, Bowie-knives, dirks, and other weapons of a similar kind. Applied to all males over the age of twenty one.
Keywords: TAX - PROPERTY OR SALES